15+6х-5х-2х^2-2*3x*(2+x)
15+6x-5x-2x^2-6x*(2+x)
15+6x-5x-2x^2-12x-6x^2
15-11x-8x^2
-8x^2-11x+15
5x(2x +1) = 0 --> x = - 0.5
25 - 100x^2 = 25*(1 - 4x^2) = 25*(1 - 2x)(1+2x) --> x 1 = +0.5 x2 = - 0.5
25x^2 - 14 = 0; 25x^2 = 14 ; x^2 = 0.56 --> x = v 0.56
2x^2 - 8 = 0; 2x^2 = 8; x^2 = 4; x1= 2; x2 = -2
4x^2 - 12=0; 4x^2 = 12; x^2 = 3 ; x = v 3
x^2 - 10x = 0 ; x(x - 10) = 0--> x = 10
4x^2 + 20x = 0; 4x(x + 5)=0--> x = - 5
2x^2 + x = 0; x(x + 1) = 0 --> x = - 1
3x^2 - 27 = 0; 3(x^2 - 9)=0; 3(x-3)(x+3)=0--> x1 = 3; x2 = - 3
4x^2 + 20x = 0; 4x(x + 5) = 0; x = - 5
-8x²-11x+15
Объяснение:
(3-х)(5+2х)-2(3х)(2+х)
15+6x-5x-2x²-12x-6x² = -8x²-11x+15